Chondroitin Sulfate Proteoglycans Negatively Modulate Spinal Cord Neural Precursor Cells by Signaling Through LAR and RPTPσ and Modulation of the Rho/ROCK Pathway. (12th May 2015) - Dyck, Scott M.; Alizadeh, Arsalan; Santhosh, Kallivalappil T.; Proulx, Evan H.; Wu, Chia-Lun; Karimi-Abdolrezaee, Soheila
Abstract: Multipotent adult neural precursor cells (NPCs) have tremendous intrinsic potential to repair the damaged spinal cord. However, evidence shows that the regenerative capabilities of endogenous and transplanted NPCs are limited in the microenvironment of spinal cord injury (SCI). We previously demonstrated that injury-induced upregulation of matrix chondroitin sulfate proteoglycans (CSPGs) restricts the survival, migration, integration, and differentiation of NPCs following SCI. CSPGs are long-lasting components of the astroglial scar that are formed around the lesion. Our recent in vivo studies demonstrated that removing CSPGs from the SCI environment enhances the potential of transplanted and endogenous adult NPCs for spinal cord repair; however, the mechanisms by which CSPGs regulate NPCs remain unclear. In this study, using in vitro models recapitulating the extracellular matrix of SCI, we investigated the direct role of CSPGs in modulating the properties of adult spinal cord NPCs. We show that CSPGs significantly decrease NPCs growth, attachment, survival, proliferation, and oligodendrocytes differentiation. Moreover, using genetic models, we show that CSPGs regulate NPCs by signaling on receptor protein tyrosine phosphate sigma (RPTPσ) and leukocyte common antigen-related phosphatase (LAR). Intracellularly, CSPGs inhibitory effects are mediated through Rho/ROCK pathway and inhibition of Akt and Erk1/2 phosphorylation. Downregulation of RPTPσ and LAR and blockade of ROCK in NPCs attenuates the inhibitory effects of CSPGS. Our work provide novel evidence uncovering how upregulation of CSPGs challenges the response of NPCs in their post-SCI niche and identifies new therapeutic targets for enhancing NPC-based therapies for SCI repair. Stem Cells 2015;33:2550–2563